A new dynamic geometric approach for empirical analysis of financial ratios and bankruptcy. - Bahiraie, Alireza; Abdul Karim, Mohd Azhar; Ibrahim, Noor Akma (American Institute of Mathematical Sciences, 2011)
This paper presents a complementary technique for the empirical analysis of nancial ratios and bankruptcy risk using nancial ratios. Within this new framework, we propose the use of a new measure of risk, the Dynamic Risk Space (DRS) measure. We provide evidence of the extent to which changes in values for this index are associated with changes in each axis's values and how this may alter our economic interpretation of changes in patterns and directions. In addition, this model tends to be generally useful for predicting nancial distress and bankruptcy. This method would be a general methodological guideline associated with nancial data, solving some methodological problems concerning nancial ratios such as non-proportionality, nonasymmetry and non-scaled. To test the procedure, Multiple Discriminant Analysis (MDA), Logistic Analysis (LA) and Genetic Programming (GP) are employed to compare results by common and modied ratios for bankruptcy prediction. Classication methods outperformed using the DRS approach.